Monitoring forest biodiversity : improving conservation through ecologically responsible management - Gardner, Toby (Earthscan forest library., 2010)
The fate of much of the world's terrestrial biodiversity depends upon our ability to improve the management of forest ecosystems that have already been substantially modified by humans. Monitoring is an essential ingredient in meeting this challenge, allowing us to measure the impact of different human activities on biodiversity and identify more responsible ways of managing the environment. Nevertheless many biodiversity monitoring programs are criticised as being little more than "tick the box" compliance exercises that waste precious resources and erode the credibility of science.